Managing complex projects and programs : how to improve leadership of complex initiatives using a third-generation approach - Heaslip, Richard J., 1955- (John Wiley & Sons Inc., 2014)
"Manage projects and programs with an innovative new framework that rethinks complex endeavorsDespite being a major process in PMI's body of knowledge and having its own standard document and certificate designation based on successful experience and passing of an exam, program and project management remains one of the most difficult concepts to master successfully in today's increasingly complex and ever-evolving global business environment. Third Generation Programmatics walks readers through where program management began, through current cutting-edge concepts, such as agile and extreme project management, and, finally, to a new set of guidelines that will allow the successful integration of programs and projects into the strategic direction of an organization. Presented through insightful vignettes and real-world case studies, the information provided in Third Generation Programmatics is essential reading not only for program and project managers in the trenches, but also for managers and executives who need to ensure the true integration of these processes into their overall business strategy. Focuses on aligning projects and programs within the complex environments of today's business models Presents a framework for best practices based on successes and failures in real-world cases Progresses from original project management frameworks through current initiatives Builds a new map for successful project and program management If you're a program or project manager, a general business manager, or a candidate for the PgMP exam, Third Generation Programmatics offers the latest, most inventive framework for ensuring the success of your organization's strategic goals"--